ChemInform Abstract: Regioselectivities in Fe(III)‐Catalyzed Cycloisomerization Reactions of γ‐Allenyl Alcohols. Issue 21 (6th May 2016) - Kim, Jae Hyung; Kim, Seung Wook; Jung, Min Seok; Ahn, Kwang‐Hyun; Kang, Eun Joo
Abstract: Tetrahydrofurans are prepared by intramolecular hydroalkoxylation of allenes via regioselective 5‐exo cyclization.